Endohedral fullerenes for organic photovoltaic devices - Ross, Russel B.; Cardona, Claudia M.; Guldi, Dirk Michael; Sankaranarayanan, Shankara Gayathri; Reese, Matthew O.; Kopidakis, Nikos; Peet, Jeff; Walker, Bright; Bazan, Guillermo C.; Van Keuren, Edward; Holloway, Brian C.; Drees, Martin (Nature Materials, 2009)
So far, one of the fundamental limitations of organic photovoltaic (OPV) device power conversion efficiencies (PCEs) has been the low voltage output caused by a molecular orbital mismatch between the donor polymer and acceptor molecules. Here, we present a means of addressing the low voltage output by introducing novel trimetallic nitride endohedral fullerenes (TNEFs) as acceptor materials for use in photovoltaic devices. TNEFs were discovered in 1999 by Stevenson et al.; for the first time derivatives of the TNEF acceptor, Lu 3 N@C 80, are synthesized and integrated into OPV devices. The reduced energy offset of the molecular orbitals of Lu 3 N@C 80 to the donor, poly(3-hexyl)thiophene (P3HT), reduces energy losses in the charge transfer process and increases the open circuit voltage (Voc) to 260 mV above reference devices made with [6,6]-phenyl-C 61 -butyric methyl ester (C 60 -PCBM) acceptor. PCEs >4% have been observed using P3HT as the donor material. This work clears a path towards higher PCEs in OPV devices by demonstrating that high-yield charge separation can occur with OPV systems that have a reduced donor/acceptor lowest unoccupied molecular orbital energy offset.